Penerapan Metode Cause-Effect Graphing dalam Pengujian Black-Box Aplikasi Kinerja Politeknik Negeri Sriwijaya - Nurul Ilma Hasana Kunio; Malahayati; Neneng Miskiyah; Dzaky Hanifah Ahmad; Siti Kamila (Jurnal ICT: Information Communication & Technology, 2026)
The Sriwijaya State Polytechnic Performance Application is used to support the integrated monitoring of performance data. The complexity of system functions and the large number of input combinations may cause errors that affect the accuracy of information. Software testing is required to ensure that all system functions operate in accordance with user requirements. This study aims to apply the Cause-Effect Graphing method in black-box testing of the Sriwijaya State Polytechnic Performance Application to identify the relationships between input conditions and system outputs and to generate effective test scenarios. The research method consists of identifying testing requirements, determining causes and effects, constructing cause-effect graphs, developing decision tables, and conducting testing on the main features of the application. The results indicate that the Cause-Effect Graphing method is capable of producing systematic test scenarios that cover various combinations of input conditions. The testing results show that the application functions operate in accordance with the system requirements. Therefore, the implementation of the Cause-Effect Graphing method can improve the effectiveness of black-box testing and support the software quality of the Sriwijaya State Polytechnic Performance Application.